Fatores de virulência e infecção epitelial in vitro de biofilmes simples e mistos de Cndida albicans, Staphylococcus aureus sensível (MSSA) e resistente à meticilina (MRSA) - Zago, Chaiene Evelin [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to evaluate, in vitro, the interaction between C. albicans and methicillinsusceptible (MSSA) and resistant (MRSA) S. aureus in relation to some of their major virulence factors. These factors were analyzed considering the three microorganisms in single and dual cultures. The interaction between these microorganisms was evaluated by counting colony-forming units (CFU/mL), analysis of metabolic activity by the XTT assay and quantification of the total biomass by crystal violet dye at 90 minutes, 12, 24, and 48 hours. To analyze the production of proteinase (SAP) and phospholipase (PL-C), fluorometric kits were used. The structure of the biofilms was acessed by scanning electron microscopy (SEM). Further, single and dual cultures of microorganisms were used to infect a reconstituted human oral epithelium (RHOE). The pattern of colonization and invasion of the RHOE was evaluated after 24 hours using the in situ hybridization technique (PNA-FISH). The damage caused by microorganisms in the tissue was evaluated by quantification of the lactate dehydrogenase enzyme (LDH) released. Molecular techniques (RT-qPCR) were also used to quantify the number of microorganisms colonizing the epithelium and to evaluate the expression of virulence genes. Gene expression was evaluated in biotic (RHOE) and abiotic (24-well polystyrene microplate) surfaces for single and dual cultures. The results from quantification assays were compared using two-way ANOVA with Tukey post-hoc test, while data from enzymatic activities were analyzed by one-way Welch-ANOVA followed by Games-Howell post hoc test. The results of gene expression were analyzed by one-way ANOVA with Tukey for data satisfying the assumptions of normality and homoscedasticity or one-way Welch-ANOVA followed by Games-Howell for heteroscedastic data. LDH results were also...(Complete abstract electronic access below)

O objetivo do presente estudo in vitro foi avaliar a interação entre os microorganismos C. albicans, S. aureus sensível (MSSA) e resistente (MRSA) à meticilina com relação a alguns dos seus principais fatores de virulência. Estes fatores foram analisados considerando os micro-organismos isoladamente e em culturas mistas. Foi verificada a interação entre esses micro-organismos através da contagem do número de colônias viáveis (UFC/mL), análise da atividade metabólica por meio do ensaio XTT e quantificação da biomassa total por meio do corante cristal violeta nos tempos de 90 minutos, 12, 24 e 48 horas. Para análise da produção de proteinase (SAP) e fosfolipase (PL-C), kits fluorimétricos foram utilizados. A estrutura dos biofilmes foi avaliada por microscopia eletrônica de varredura (MEV). Culturas simples e mistas dos micro-organismos também foram utilizadas para infectar um epitélio oral humano reconstituído (EOHR). A capacidade de colonização e invasão foi avaliada após 24 horas utilizando a técnica de hibridização in situ (PNA-FISH). A avaliação do dano causado pelos micro-organismos ao tecido foi realizada por quantificação da liberação da enzima lactato desidrogenase (LDH). Técnicas moleculares (RT-qPCR) foram empregadas para quantificação do número de micro-organismos colonizando o epitélio e também para avaliação da expressão de genes de virulência. A expressão gênica foi avaliada em superfície biótica (EOHR) e abiótica (placa de poliestireno de 24 poços) para culturas simples e mistas dos micro-organismos. Os resultados dos ensaios de quantificação foram analisados utilizando ANOVA a dois critérios com teste post-hoc de Tukey (α = 0,05), enquanto os dados de atividade enzimática foram analisados por ANOVA a um critério com correção de Welch seguido pelo teste de Games-Howell. Os resultados da expressão gênica foram... (Resumo completo clicar acesso eletrônico)
Keywords: Zircônio; Candida albicans; Staphylococcus aureus; Biofilme; Fosfolipases; Proteinase; Coinfecção